Sustainability of bio-jetfuel in Malaysia - Roda, Jean-Marc; Goralski, Maxime; Benoist, Anthony; Baptiste, Anaphel; Boudjema, Valentine; Galanos, Theodoros; Georget, Marine; Hévin, Jean-Eudes; Lavergne, Simon; Eychenne, Frédéric; Liew, Kan Ern; Schwob, Cyrille; et al. (Centre of International Cooperation in Agronomy Research for Development (CIRAD), 2015)
Aviation represents a small but growing share of global CO2 emissions (2-3%), and Southeast Asia is where this industry grows the fastest. The industry targets 50% reduction in net CO2 emission by 2050, and will need at least 2 million tonnes of biofuel by 2020. In Southeast Asia, competition between natural spaces (such as tropical forests) and biofuel development should be avoided. A complex interaction of political, sociological and natural factors influence the logistics, the infrastructures and the potential sustainability of biofuel. The contrasted growing conditions, and the geographically scattered nature of the potential resources for aviation industry, add to the complexity. Building visions and actions necessitates a range of assessments and researches, to insure sustainability of appropriate scenarios and pathways. In Malaysia, a consortium established a Center of Excellence on Biomass Valorisation for aviation, in order to study the biomass feedstocks and pathways which are necessary to meet the industry target, and to ensure sustainability.